RESHAPING EDUCATION IN THE AFTERMATH OF CONFLICT: UNDERSTANDING THE DYNAMICS OF INTERNAL DISPLACEMENT AND SECONDARY EDUCATION IN DISTRICT SWAT, PAKISTAN - Zainab, Hazrat; Ahmad, Dr. Nasir; Hussain, Dr. Sajjad (JELM, 2025)
This study aims to analyze the impact of conflict and internal displacement on secondary education in Swat, Pakistan and how this conflict has provided and opportunity for the development of educational landscape. The participants of the study were all the schoolteachers who had teaching experience of more than twenty years at secondary schools in district swat, Pakistan. Data was collected through semi structured interview from 20 participants. The collected information was categories into various themes based on interview questions. This study concluded that this conflict and internal displacement had a significant adverse effect on the lives of secondary school students. However, it was also found that this conflict also proved an opportunity for school education. Schools have been rebuilt to international standards, equipped with all facilities. The new school buildings provide more space with additional classrooms. The study also found a significant increase in student enrolment. The study recommended that government department, non-governmental organizations, local communities, Parents, and teachers may be involved for the improved and sustainable education.